Postrzeganie problematyki środowiskowej w funkcjonowaniu małych i średnich przedsiębiorstw w Polsce - wybrane aspekty - Becla, Agnieszka (Perception of environmental problems by small and medium-sized enterprises in Poland - selected aspects, 2006)
The article is composed of four parts. In the first part the author identifies the notions of small and medium-sized enterprises and their attributes. In the second part she presents the current economic, financial and social situation of these enterprises in Polish economy. The third part includes treatment of ecological problems in the enterprises activity from the theoretical point of view. In the fourth part of the article the author presents methods of identification and solution of ecological challenges in Polish small and medium-sized enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 33-49